Implikasi Penyalagunaan Wewenang Administrasi Dalam Seleksi Perangkat Desa Kabupaten Demak - Muhamad Azhar (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
Abstract This study aims to find out how the implications of the abuse of Administrative Authority in the Village Apparatus Selection in Demak Regency. The research is a concise study based on cases that were consulted at the Legal Consultation Board, Faculty of Law, University of Diponegoro. Research Results Aimed that the abuse of authority occurred in the process of selecting village officials in Demak Regency. The authority to determine the selection committee of the village apparatus is the authority of the Village Head as mandated by the Law - Invitation on the Village, and not the authority of the Regent of Demak Regency. Keywords: Power Utilization, Village Officials, Demak Regency. Abstrak Penelitian ini bertujuan untuk mengtahui bagaimana implikasi penyalagunaan Wewenang Administrasi Dalam Seleksi Perangkat Desa di Kabupaten Demak. Penelitian merupakan kajian ringkas berdasarkan pada kasus yang dikonsultasikan pada Badan Konsultasi Hukum, Fakultas Hukum Universitas Diponegoro. Hasil Penelitian Menujukan bahwa penyalagunaan wewenang terjadi pada proses seleksi perangkat desa di Kabupaten Demak. Kewenangan untuk menetapkan panitian seleksi perangkat desa merupakan kewenangan dari Kepala Desa sebagaimana amanat Peraturan Perundang – Undangan tentang Desa, dan bukan berada pada kewenangan Bupati Kabupaten Demak. Kata Kunci: Penyalagunaan Wewenang, Perangkat Desa, Kabupaten Demak.